LESSONS FOR UNIVERSITY TEACHER - Alevtina S. Robotova (Moscow Polytechnic University, 2016)
The author analyzes her own experience in designing master courses in pedagogy. The paper focuses on the challenges the university teachers face in their everyday practice. Postgraduate students stimulate a teacher to continuous self-education. This work demands persistent self-reflection, self-contemplation, and self-examination in order to reveal gaps in knowledge and to update it according to a new context of learning and teaching. A teacher should percept the necessity of himself (herself) using the words of M. Mamardashvili, and the first that he (she) has to do is to learn carefully the expectations of students and on this basis to design the MA course.